Strategy to Increase The Competitiveness of National Salt in Indonesia - Arif Haendra; M. Syamsul Maarif; Joko Affandi; Anggraini Sukmawati (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Salt is a strategic commodity and political commodity in Indonesia. However, during the research period, namely in 2015-2019, the national salt production has not been able to meet the demand for salt. This has resulted in national salt consumption still being dependent on imports. This results in a potential dependence on imported salt which can hamper the competitiveness of domestic salt. Local people are increasingly cornered and find it difficult to be competitive. This study aims to analyze the competitiveness of the national salt industry and formulate efforts to increase the competitiveness of the national salt industry. The method used in this research is the Revealed Comparative Advantage (RCA) and Revealed Symmetric Comparative Advantage (RSCA) analysis and the Analytical Hierarchy Process (AHP) method which is one of the analytical tools used to assist managerial decision-makers. The data used in this study are primary data in the form of interviews and questionnaires and secondary data obtained from literature studies. The results showed that the salt commodity was not competitive. This is because Indonesia's salt commodity does not have a comparative advantage. Keywords: AHP, competitiveness, salt industry, RCA, strategy